THE ROLE OF DANCING AS LEISURE ACTIVITY IN AESTHETIC EDUCATION OF STUDENTS 8 TO 10 YEARS - Salup Mărioara; Jacek Sobon (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Activity in the lessons of modern dance, using appropriate music and features of age, is a way of activation of children in the educational process. Modern dance teacher's personality, creativity, willingness to search and to promote the new, blending the work of training everything is good with what is beautiful, our own childhood memories bringing us closer to the age of the children that we educate, to their requirements, through all of this we can increase efficiency of modern dance classes, to ensure harmonious development, the formation of custom and pleasure to practice systematically elements of modern dance. Using music in modern dance classes at primary school will increase efficiency and in particular its density, and the dynamic of the lessons will get a new look that can be considered for enrichment of the methods used in educational process. The purpose of this study is to record the steps of modern dance to children in primary and the efficiency analysis using music lesson in modern dance lessons.